Validation of the recrossing-algorithms for the numerical simulations of multichannel electronic transitions to the degenerate states of an acceptor - Feskov, S.V. (Numerical Methods and Programming (Vychislitel'nye Metody i Programmirovanie), 2017)
The multichannel electron transfer from the donor compound of a molecular system to a set of the degenerate states of an acceptor is considered within the Zusman-Bixon-Jortner model. An expression for the probability of transition to each of the acceptor states from the delta-localized state on the donor is obtained using the Green’s function technique. Correctness of two recrossing-type numerical algorithms is analyzed by comparing the expected frequencies of transitions to different product states with the calculated probabilities. The numerical schemes are tested using the QM2L software package.